2017
DOI: 10.1021/acs.langmuir.6b04295
|View full text |Cite
|
Sign up to set email alerts
|

Hydrophobic Nanoparticles Reduce the β-Sheet Content of SEVI Amyloid Fibrils and Inhibit SEVI-Enhanced HIV Infectivity

Abstract: Semen-derived enhancer of virus infection (SEVI) fibrils are naturally abundant amyloid aggregates found in semen that facilitate viral attachment and internalization of human immunodeficiency virus (HIV) in cells, thereby increasing the probability of infection. Mature SEVI fibrils are composed of aggregated peptides exhibiting high β-sheet secondary structural characteristics. Herein, we show that polymers containing hydrophobic side chains can interact with SEVI and reduce its β-sheet content by ∼45% compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 61 publications
0
18
0
Order By: Relevance
“…99 . A nanoparticle formulation of this hydrophobic polymer reduced SEVI-mediated enhancement of HIV infection in cell culture experiments.…”
Section: Semen Amyloid Antagonistsmentioning
confidence: 99%
“…99 . A nanoparticle formulation of this hydrophobic polymer reduced SEVI-mediated enhancement of HIV infection in cell culture experiments.…”
Section: Semen Amyloid Antagonistsmentioning
confidence: 99%
“…The high-level association β-sheet secondary structure in proteins has been confirmed to be a distinguishing feature in the formation of the protein aggregates and amyloid fibrils in many diseases ( Nabers et al, 2016 ). A highly stable cross-β-sheet secondary structure of amyloid fibrils is usually identified by CD spectra assay ( Sheik et al, 2017 ). However, PAP248-286 monomer lacks a significant proportion of ordered cross-β-sheet structure ( Figure 2D ).…”
Section: Discussionmentioning
confidence: 99%
“…These nanoparticles and polymers were far more efficient for inhibiting SEVI‐enhanced HIV infection than monomeric and pentameric 6‐methylbenzothiazole aniline, proposing a critical role of steric hindrance in the design of effective SEVI neutralizing agents. A very recent study suggested that a nanoparticle formulation of hydrophobic polymers diminished SEVI amyloid‐mediated HIV infection, and that the use of hydrophobic interactions to alter structures of amyloid fibrils at the level of the secondary structures may be an useful approach to neutralize the SEVI function …”
Section: Inhibition Of Sevi‐enhanced Hiv Viral Infectionmentioning
confidence: 99%
“…A very recent study suggested that a nanoparticle formulation of hydrophobic polymers diminished SEVI amyloid-mediated HIV 31 infection, and that the use of hydrophobic interactions to alter structures of amyloid fibrils at the level of the secondary structures may be an useful approach to neutralize the SEVI function. 52…”
Section: Development Of Agents To Suppress Hiv Interaction With Sevi mentioning
confidence: 99%